Lagrangian relaxation

From Glossary

Jump to: navigation, search


The removal of constraints and putting them into the objective as in the Lagrangian function. Specifically, suppose we have

LaTeX: \max \{ f(x): x \in X, \, g(x) \le 0, \, h(x) = 0\}.

The Lagrangian relaxation is

LaTeX: \max \{f(x) - u^T g(x) - v^T h(x): x \in X\},

where LaTeX: u \ge 0 (LaTeX: v is unrestricted).

This is a relaxation of the original mathematical program because the constraints have been removed (expanding the feasible region), and for LaTeX: x feasible (i.e., satisfying these constraints), the relaxed objective satisfies:

LaTeX: f(x) - u^T g(x) - v^T h(x) \ge f(x),

because LaTeX: v^T h(x)=0 and LaTeX: u^Tg(x) \le 0.

The objective is the usual Lagrangian function when LaTeX: X is simply LaTeX: \mathbb{R}^n. It provides a foundation for Lagrangian duality and the Generalized Lagrange Multiplier Method.

Note that LaTeX: X could retain some constraints, such as in the separable form LaTeX: X = X_1 \times \ldots \times X_n. Now suppose LaTeX: f(x) = f_1(x_1) + \ldots + f_n(x_n), LaTeX: g(x) = g_1(x_1) + \ldots + g_n(x_n), and LaTeX: h(x) = h_1(x_1) + \ldots + h_n(x_n). Then, the Lagrangian relaxation decomposes into LaTeX: n independent mathematical programs for any multiplier value:

LaTeX: \max \{f(x) - u^T g(x) - v^T h(x): x \in X\} 
= \sum_{j=1}^n \max {f_j(x_j) - u_j g_j(x_j) - v_j h_j(x_j): 
x_j \in X_j \}.


Views
Personal tools